2018
DOI: 10.1093/annweh/wxy015
|View full text |Cite
|
Sign up to set email alerts
|

Observed Differences between Males and Females in Surgically Treated Carpal Tunnel Syndrome Among Non-manual Workers: A Sensitivity Analysis of Findings from a Large Population Study

Abstract: ObjectivesWe aimed at assessing whether differences among males and females in carpal tunnel syndrome (CTS) epidemiology might be attributable to segregation with respect to occupational biomechanical exposures or differential access to care by sex.MethodsWe analysed surgically treated cases of CTS occurring among non-manual workers in Tuscany between 1997 and 2000. We conducted a Monte Carlo simulation to estimate the difference in occupational biomechanical exposures between males and females necessary to ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
17
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 50 publications
3
17
1
1
Order By: Relevance
“…Remarkably, the gender ratio usually observed for CTS (F:M 2:1) was not found in our study population and the percentage of men who had received surgery for CTS (11.8%) was actually higher than in females (8.4%). This finding strongly supports the hypothesis that most cases of CTS among ATTR patients are attributable to the disease and are not idiopathic.…”
Section: Discussioncontrasting
confidence: 79%
See 2 more Smart Citations
“…Remarkably, the gender ratio usually observed for CTS (F:M 2:1) was not found in our study population and the percentage of men who had received surgery for CTS (11.8%) was actually higher than in females (8.4%). This finding strongly supports the hypothesis that most cases of CTS among ATTR patients are attributable to the disease and are not idiopathic.…”
Section: Discussioncontrasting
confidence: 79%
“…In a recent study, the lifetime prevalence of carpal tunnel release in the general population was estimated to be as high as 3.1% . The descriptive epidemiology of CTS has constant features over time and across countries, incidence being much higher among females (with a ratio of at least 2:1) and strongly age‐related, with a characteristic peak of incidence in females aged between 40 and 60 years . CTS arises from a complex pathological process that can be determined by both occupational and personal factors.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mechanical loading seems to be a significant factor in the pathogenesis of de Quervain's disease. Nevertheless, a large population study [26] reported that women had four times more CTS than did men. The causes of diseases are most likely more complicated than simple sex differences, the combined effects of hormonal changes, and mechanical loading.…”
Section: Discussionmentioning
confidence: 99%
“…Hormonal changes are associated with musculoskeletal diseases. [27,28] A direct effect of estrogen antagonist (aromatase-inhibitor [AI]) therapy was reported [26] to induce a musculoskeletal syndrome characterized by tenosynovial change and post-treatment intra-articular fluid. [29] AI treatment is associated with a higher prevalence of CTS and trigger finger.…”
Section: Discussionmentioning
confidence: 99%